Worldwide Prevalence of Occupational Exposure to Needle Stick Injury among Healthcare Workers: A Systematic Review and Meta-Analysis - Dechasa Adare Mengistu; Sina Temesgen Tolera; Yohannes Mulugeta Demmu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Healthcare workers are at high risk of occupational exposure to needle stick injury worldwide. Occupational exposure to needle stick injury represents the most common sources of infection such as hepatitis B virus, hepatitis C virus, and human immunodeficiency virus. Thus, this review aimed to determine the career time and previous one-year global pooled prevalence of occupational exposure to needle stick injury among healthcare workers. Methods. The review considered articles written in English language and published from 2012 to 2020. The articles were searched using nine electronic databases (PubMed, Google Scholar, CINAHL, MEDLINE, Cochrane library, Web of Science, SCOPUS, MedNar, and ScienceDirect) using a combination of Boolean logic operators (AND, OR, and NOT), Medical Subject Headings, and keywords. Quality assessment was performed to determine the relevance of the articles using Joanna Briggs Institute critical appraisal tools. Several steps of assessment and evaluation were taken to select and analyze the relevant articles. Results. The worldwide pooled prevalence of needle stick injuries among healthcare workers during career time and previous one year was 56.2% (95% CI: 47.1, 64.9) and 32.4% (95% CI: 22.0, 44.8), respectively. The career time pooled prevalence of needle stick injuries based on the socioeconomic development and study area was 54.8% and 55.1%, respectively, and one-year pooled prevalence of needle stick injury was 26.0% and 20.9%. Conclusion. The review found a high prevalence of occupational exposure to needle stick injury among healthcare workers and suggests the need to improve occupational health and safety services in the healthcare systems.